2009
DOI: 10.1038/npp.2009.195
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Progesterone in Menstrual Cycle-Related Variability in Prepulse Inhibition in Healthy Young Women

Abstract: Prepulse inhibition (PPI) of the startle response is sensitive to sex, with healthy young women showing less PPI compared with age-matched men, and varies according to the menstrual cycle phase in women. Relatively less is known regarding sex and hormonal influences in prepulse facilitation (PPF). Menstrual phase-related variability in PPI is suggested to be mediated by fluctuating estrogen level, based on the observations of more PPI in women during the follicular, relative to the luteal, phase. No study has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 67 publications
4
33
4
Order By: Relevance
“…Contrary to our findings, no differences in ASR between follicular and luteal phase were reported in healthy women in several studies [43,45,46]. However, in some of these studies the investigated samples were comparatively small which would have made it harder to detect a rather minor effect.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, no differences in ASR between follicular and luteal phase were reported in healthy women in several studies [43,45,46]. However, in some of these studies the investigated samples were comparatively small which would have made it harder to detect a rather minor effect.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in another study PMDD patients showed heightened ASR during both the follicular and the luteal phase compared to healthy women while there was no difference in ASR between the two cycle phases within the PMDD or the healthy control group [44]. Similarly, Jovanovic et al [45] and Kumari et al [46] found no differences in ASR magnitudes during follicular vs. luteal cycle phase in healthy samples although a significant effect of menstrual cycle phase was found on PPI [45]. Jovanovic et al also investigated the influence of menstrual cycle phase in a longitudinal approach in 14 women.…”
Section: Introductionmentioning
confidence: 89%
“…Kumari et al 2011), with some less common exceptions in human reports, perhaps attributable to the fact that these sex differences are moderated by menstrual phase (Swerdlow et al 1997; Jovanovic et al 2004) and other factors potentially related to reproductive hormones (e.g. Bannbers et al 2010; Kumari et al 2010; Comasco et al 2015, 2016). Male > female PPI was evident in the present sample, and this group difference increased modestly when samples were limited to women of child-bearing years and to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that females tend to rate negative-valence pictures as more unpleasant than males and have greater defensive reactivity to negatively-valence pictures, as measured by a number of autonomic responses (Bradley, Codispoti, Sabatinelli, & Lang, 2001). In studies of pre-pulse inhibition, females display lesser inhibition in comparison to males (Kumari, 2003; Swerdlow, et al, 1993) and this effect has also shown to be sensitive to the menstrual phase (Kumari, et al, 2010). Considering the notable differences in defensive reactivity and sensorimotor gating between males and females, it is plausible that the relative contributions of genetic and environmental influences to startle reactivity and AMS also differ between the two sexes.…”
Section: Introductionmentioning
confidence: 99%